Transurethral en bloc resection of nonmuscle invasive bladder cancer: trend or hype. Issue 2 (March 2017) - Herrmann, Thomas R.W.; Wolters, Mathias; Kramer, Mario W.
Abstract : Purpose of review: Inherent limitations of conventional transurethral resection of bladder tumors as the standard approach for diagnosis and treatment of bladder cancer are well know: staging error because of insufficient assessment of resection depth as well as intravesical tumor fragmentation that complicates histopathological evaluation. The purpose of this review is to present recent clinical data on en bloc resection of bladder tumor (ERBT) that has been demonstrated to offer high potential to overcome these limitations. Recent findings: The recently published studies confirm the results our previous reviews for laser ERBT and current-based ERBT from 2014. ERBT provides a better resection quality with up to 95% presence lamina muscularis propria as surrogate marker for quality. It can be performed using all energy sources. Available data demonstrate with all due limitations of reporting quality no relevant difference with regard to perioperative morbidity compared with conventional transurethral resection of bladder tumors. No conclusions can be drawn regarding the impact of ERBT on recurrence as data are controversial. Summary: ERBT has gained momentum in the past years. The hypothesized advantages over conventional TURBT seem to manifestate for tumors up to 3 or 4 cm in size with regard to staging, specimen quality, and analyzability in pathological evaluation in general. The impact on recurrence remains to be defined by further studies.